2020
DOI: 10.1177/1079063220965953
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Coping Strategies of Nonoffending Pedophilic and Hebephilic Individuals From Their Online Forum Posts

Abstract: Individuals who identify as pedophilic or hebephilic, and who do not offend, are increasingly visible in online discourse and as a focus of research. Developing knowledge about this population will offer insights into their psychological needs and, potentially, into the mechanisms and strategies individuals use to live offense-free lives. This study examined coping strategies among members of an online forum supporting pedohebephilic individuals who do not wish to offend. Forum users’ posts were analyzed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…MAPs negative treatment encounters lead many to seek support in informal networks, such as via trusted friends and family, or online communities (Jones et al, 2021;Stevens & Wood, 2019). However, this leaves a gap in professional healthcare service provision, whereby genuine mental health issues remain untreated.…”
Section: Barriers To Help-seeking and Effective Treatment Accessmentioning
confidence: 99%
“…MAPs negative treatment encounters lead many to seek support in informal networks, such as via trusted friends and family, or online communities (Jones et al, 2021;Stevens & Wood, 2019). However, this leaves a gap in professional healthcare service provision, whereby genuine mental health issues remain untreated.…”
Section: Barriers To Help-seeking and Effective Treatment Accessmentioning
confidence: 99%
“…This is consistent with Rosenmann and Safir’s (2006) hypothesis that with the development of online communities, individuals with paraphilias may begin to forgo seeking out professional help. It has been observed that virtual spaces have the potential to promote non-offending sentiments (see e.g., Jones et al, 2021), and to encourage individuals to seek additional support from family members (“It was through the community that I then decided to tell my dad”). Nevertheless, by relying exclusively on peer-to-peer online communities and not seeking professional help, individuals with pedophilia would be missing the opportunities granted by a face-to-face evaluation, such as the assessment of other contextual factors, or receiving empirically-based interventions from a professional.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, while studying the online subculture of individuals with pedophilia, Holt et al (2010) found that “virtual self-disclosure” and sharing personal views and experiences on certain dedicated online forums, accessed by professed individuals with pedophilia, allowed them to “share aspects of their lives that were otherwise not possible in the real world” (p. 10). For individuals with pedophilia who want to stay offense-free, some ‘anti-contact’ online spaces can provide the opportunity to reinforce the idea that sexual behavior with minors is unacceptable (Cantor & McPhail, 2016; Jones et al, 2021). However, involvement in online communities that foment adult-minor sexual contact can lead to the further normalization of pedophilia and the reinforcement of deviant behavior (see e.g., Quayle & Taylor, 2011; Taylor et al, 2001).…”
Section: Accessing This Population: the Use Of Blogsmentioning
confidence: 99%
“…There is a need for a validation study of the IASI rev. Furthermore, at this state of research, case studies and qualitative research would help to understand this construct and its impact on individuals better (see Jones et al, 2020 for qualitative research giving some insights into acceptance of pedophilia as a coping strategy of individuals who identify as pedophilic or hebephilic and do not offend). Quantitative research is needed in order to study how closely acceptance of SIM is related to measures of other constructs like the Unconditional Self-Acceptance Questionnaire ( Chamberlain and Haaga, 2001 ), the Emotional Processing Scale ( Baker et al, 2015 ), and/or the Thought Control Questionnaire ( Wells and Davies, 1994 ).…”
Section: Discussionmentioning
confidence: 99%